DEVELOPMENT OF DUAL-SWITCHES BRIDGELESS PFC TOTEM-POLE SEPIC CONVERTER FOR LED DRIVER APPLICATION (Jurnal Teknologi (Sciences & Engineering), 2024)
This paper presents a Dual-Switch Bridgeless Power Factor Correction (DSBPFC) Single Ended Primary Inductor Converter (SEPIC) with Totem-Pole circuit structure for LED Driver Application. The conventional Full-Bridge Rectifier (FBR) SEPIC converter has five diodes, four in the rectifier bridge and one in the SEPIC. In addition, the FBR SEPIC converter has several drawbacks, including low power factor (PF), high current harmonics (THDi), and high output voltage ripple, due to the combination of two operation circuits in a single converter structure. The proposed DSBPFC SEPIC converter with Totem-Pole method improves PF and reduces THDi and output voltage ripple compared to the conventional FBR SEPIC. Additionally, it only requires three diodes instead of five. The optimization parameter design minimizes the THDi and output voltage ripple. In addition, to improve the quality of the AC source, the inductors are designed to operate in DCM and CCM based on the ripple-balancing concept between input and output inductors. As to reduce output voltage ripple, a high capacitance of output capacitor is used. The simulation result of the THDi is 3.8% whereas the experimental result shows that the THDi is 23.5%; which can be attributed to the parasitic elements at the passive components. Furthermore, the experimental results of the output voltage ripple are 2 V with output capacitance of 3300 μF, compared to the output voltage ripple of 4.40 V for 470 μF. Therefore, the proposed converter's design is confirmed with an output power of approximately 14.4 W.